A Review on the Pharmacological Aspects of Engeletin as Natural Compound - Zhong X; Huang R; Chen X; Lei Y (Dove Medical Press, 2023)
Xing Zhong,1,* Rui Huang,2,* Xin Chen,2 Yuhua Lei2 1Cardiovascular Disease Center, Central Hospital of Enshi Tujia and Miao Autonomous Prefecture, Hubei Minzu University, Enshi, People's Republic of China; 2Cardiovascular Disease Center, Central Hospital of Enshi Tujia and Miao Autonomous Prefecture, Enshi, People's Republic of China*These authors contributed equally to this workCorrespondence: Yuhua Lei, Email yuhualei0319@163.comBackground: Engeletin (ENG) is a natural flavonoid compound known for its diverse physiological and pharmacological effects, such as anti-inflammatory, antioxidant, and immunomodulatory properties. It has garnered significant attention as a promising candidate for drug development.Objective: This article aims to comprehensively review the clinical application, pharmacological action, and potential mechanisms of ENG, while exploring its prospects in clinical pharmacology.Methods: We conducted a systematic search of PubMed, Science Direct, Google Scholar, Web of Science, Scopus, and MEDLINE for a thorough review of high-quality articles on the source, extraction, and application of ENG, or the primary active ingredient for improving bodily injuries.Results: ENG exhibits significant potential in treating a variety of diseases across different systems, attributed to its anti-inflammatory, antioxidant, anti-tumor, and metabolic regulatory activities. These effects are linked to direct or indirect interactions with multiple pathways involving key molecules upstream and downstream.Conclusion: While ENG shows promise, its development requires further exploration. Future studies should focus on elucidating its mechanisms of action, identifying targets through clinical studies, and optimizing compounds for drug development. These research directions are crucial for advancing the development and application of flavonoids. This review underscores the significant research potential of ENG, paving the way for its application in diverse clinical settings.Keywords: engeletin, pharmacological, agent, liliaceous plants